2007
DOI: 10.1254/jphs.fp0070770
|View full text |Cite
|
Sign up to set email alerts
|

p38 Mitogen-Activated Protein Kinase Contributes to Angiotensin II-Stimulated Migration of Rat Aortic Smooth Muscle Cells

Abstract: Abstract. In this study, we clarified the intracellular mechanism of angiotensin II (Ang II) in promoting migration in rat aortic smooth muscle cells (RASMCs). RASMC migration was measured with the Boyden chamber assay, and the result was confirmed with an aortic sprout assay. The activities of kinases were investigated by western blot analysis. Ang II enhanced RASMC migration, which was chemotaxis directed, and induced the phosphorylation of p38 mitogen-activated protein kinase (MAPK), extracellular signal-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 33 publications
3
22
1
Order By: Relevance
“…The growth inhibitory effect of the AT2 receptor is mediated by protein tyrosine phosphatase activation, which inhibits activation of MAP kinases (Bedecs et al, 1997;. Ang II stimulates the activation of MAP kinases, including ERK1/2, p38 and JNK in VSMCs (Touyz et al, 1999;Mabrouk et al, 2001;Lee et al, 2007). ERK1/2 and p38 activation play important roles in Ang II-induced VSMCs proliferation (Wilkie et al, 1997;Viedt et al, 2000;Zhao et al, 2002;Lee et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The growth inhibitory effect of the AT2 receptor is mediated by protein tyrosine phosphatase activation, which inhibits activation of MAP kinases (Bedecs et al, 1997;. Ang II stimulates the activation of MAP kinases, including ERK1/2, p38 and JNK in VSMCs (Touyz et al, 1999;Mabrouk et al, 2001;Lee et al, 2007). ERK1/2 and p38 activation play important roles in Ang II-induced VSMCs proliferation (Wilkie et al, 1997;Viedt et al, 2000;Zhao et al, 2002;Lee et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Ang II stimulates the activation of MAP kinases, including ERK1/2, p38 and JNK in VSMCs (Touyz et al, 1999;Mabrouk et al, 2001;Lee et al, 2007). ERK1/2 and p38 activation play important roles in Ang II-induced VSMCs proliferation (Wilkie et al, 1997;Viedt et al, 2000;Zhao et al, 2002;Lee et al, 2007). Zhao et al (2002) reported that simultaneous upregulation of c-Jun and c-Fos proteins is crucial for VSMCs proliferation, and p38 MAP kinase have additive effects on both the induction of c-Jun expression and VSMCs proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that activation of the p38 MAPK signaling pathway by the contractile agonists angiotensin II, 33,34) vasopressin, 35) and endothelin-1 36) results in actin remodelingdependent tension development through downstream phosphorylation of HSP27 in VSMCs. 37) In the present study, we found that a selective p38 MAPK inhibitor SB203580 not only attenuated the contractile response to hyperosmotic stress but also inhibited the hyperosmolarity-induced increase in the F-actin/G-actin ratio, suggesting that hyperosmotic stress induces vasoconstriction via p38 MAPK-mediated actin polymerization, probably through the same downstream pathway as described above.…”
Section: Discussionmentioning
confidence: 99%
“…31,37,38 Ang IIinduced ERK1/2 and p38 activation is increased in SHR vasculature 39 and ERK1/2 and p38 activation have important roles in Ang IIinduced VSMCs proliferation. 37,40,41 In these previous studies, the downregulatory effect of CCL5 on Ang II-induced SHR VSMCs proliferation was mediated by inactivation of p38, 25 and the expression of CXCL8 by Ang II was mediated by ERK1/2 MAP kinase activation. 8 A potent JNK-activating effect of Ang II was demonstrated in rat aortic cells including VSMCs.…”
Section: Discussionmentioning
confidence: 99%